Retinal astrocytic hamartomas: 2 cases of atypical clinical presentation - Bouteleux, V.; Tick, S.; El Chehab, H.; Mendes, M.; Agard, E.; Russo, A.; Dot, C. (Acta ophthalmologica (Oxford, England), 2016)
Purpose Retinal astrocytic hamartomas (RAH) are rare benign tumors found mainly in patients with phacomatosis. In these cases, RAH is a major diagnosis criteria. Methods We report the cases of two patients with 2 different clinical presentations. Results The case 1 is an asymptomatic man without medical history. A voluminous white retinal lesion is discovered incidentally. The ultrasound shows intratumoral calcifications and autofluorescence imaging shows hyperautofluorescent calcified beads. Characteristic moth‐eaten spaces are seen on the SD‐OCT. The final diagnosis is isolated RAH. The case 2 is a 56 year old woman suspected of neurofibromatosis (NF) type 2. The fundoscopy found in both eyes a peripapillary whitish flat retinal lesion with blurred edges located on the surface of the retina. There is no autofluorescence nor hyperfluorescence. The diagnosis of plane RAH (= type 1) is made given the context. Conclusions RAH must be known because of the impact on phacomatosis diagnosis. RAH are associated with Tuberous Sclerosis Complex in about 55% of cases and with NF type 1 and type 2 in 15% of cases. Nevertheless in 1/3 of cases it occurs in healthy subjects. Three types of RAH have been described (plan (case 1), multinodular (case 2) and intermediate). Classical appearance (=type II) is a yellowish nodular ‘mulberry‐like’ tumor. It is autofluorescent and hyperfluorescent in late frames of angiography. However, there are less typical presentations which is reported in case 2 and which makes discuss differential diagnosis. RAH can be a difficult diagnosis for which the clinical history and the multimodal imaging are essential. Neurological opinion and cerebral imaging should complete the investigation to search other diagnosis criteria of phacomatosis before concluding in an isolated form.